AIR VELOCITY PROFILES IN AIR BLAST FREEZERS FILLED WITH BOXES OF FRUIT PULP MODELS - Resende, J.V.; Silveira Jr., V. (Revista de Engenharia Térmica, 2004)
The changes in the air velocities caused by the resistance for the air flow due to fruit pulp model packaged (100 grams) and conditioned in multi layers boxes during freezing process were evaluated and air flow rate were estimated using a method of treatment of the experimental data. The air velocities were measured before the air pass through the pillage of multi layer boxes in the air stream. For the measurements processing was used a non linear regression routine. Air flow rate measured by the present method resulted of the numerical integration of air velocities adjusted profile. Results presented a relative difference 10 % higher than the standard average procedure, which consists in averaging the air velocity measurements performed at each point of the section. In the same fan operation conditions, the results shown for the 7 layers arrays of product in the boxes which the air velocity was 62% lower than the 3 layers arrays and 50.9 % lower than the 5 layers arrays of product. These results were proportional to the bulk area for the air flow.